Strategi Pengembangan Agrowisata Hidden Paradise Di Desa Suluan Kecamatan Tombulu Kabupaten Minahasa - Wenas, Alexander; Ruauw, Eyverson; Loho, Agnes Estephina (Sam Ratulangi University, 2023)
The purpose of this study was to identify appropriate strategies in the development of Hidden Paradise agro-tourism area in Suluan village, Tombulu sub-district, MInahasa Regency. This research was conducted from October to December 2022. The sampling method used purposive sampling and accidental sampling methods. Primary data was obtained directly from respondents by conducting direct interviews using questionnaires to owners, employees, and visitors of Hidden Paradise Minahasa Agrotourism so that the total number of respondents was 30 people. Secondary data obtained from the Central Bureau of Statistics, and Tombulu District data. Secondary data is also obtained from the internet with the topic of this research which is Agrotourism Development Strategy. The analysis method used in this research is SWOT analysis. The results showed that the Hidden Paradise Minahasa Agrotourism Development Strategy in Suluan Village, Tombulu District, Minahasa Regency is at the coordinate point 0.73; 0.47 which is in quadrant I which means that the position supports a growth strategy.